2007
DOI: 10.1111/j.1365-246x.2007.03549.x
|View full text |Cite
|
Sign up to set email alerts
|

Crustal structure of the Newfoundland rifted continental margin from constrained 3-D gravity inversion

Abstract: A B S T R A C TThe rifting history of the Atlantic continental margin of Newfoundland is very complex and so far has been investigated at the crustal scale primarily with the use of 2-D seismic surveys. While informative, the results generated from these surveys cannot easily be interpreted in a regional sense due to their sparse sampling of the margin. A 3-D gravity inversion of the free air data over the Newfoundland margin allows us to generate a 3-D density anomaly model that can be compared with the seism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 38 publications
3
35
0
Order By: Relevance
“…Regarding the Grav3D software itself, several studies have confirmed that it is able to recover the information from synthetic models (Cella et al, 2007;Dutra and Marangoni, 2009;Li and Yang, 2011); inverted density structures have been reported for the shallow structure of the Somma-Vesuvius volcano (Cella et al, 2007), Central Brazil (Dutra and Marangoni, 2009), North China (Li and Yang, 2011), the Newfoundland continental margin (Welford and Hall, 2007) and the Irish Atlantic continental margin (Welford et al, 2010). Using the density anomaly model as reference and the parameters outlined above, we obtained the 3-D density model doubly constrained by seismic velocities and gravity data that is shown in Fig.…”
Section: Assessment Of Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Regarding the Grav3D software itself, several studies have confirmed that it is able to recover the information from synthetic models (Cella et al, 2007;Dutra and Marangoni, 2009;Li and Yang, 2011); inverted density structures have been reported for the shallow structure of the Somma-Vesuvius volcano (Cella et al, 2007), Central Brazil (Dutra and Marangoni, 2009), North China (Li and Yang, 2011), the Newfoundland continental margin (Welford and Hall, 2007) and the Irish Atlantic continental margin (Welford et al, 2010). Using the density anomaly model as reference and the parameters outlined above, we obtained the 3-D density model doubly constrained by seismic velocities and gravity data that is shown in Fig.…”
Section: Assessment Of Resultsmentioning
confidence: 96%
“…Conversely, the inversion for a density anomaly structure or inverse modeling implies generating a model that fits the observed gravitational field in the subsurface, even though the resulting model is non-unique and simply represents one of many models that can satisfy the observations (Welford and Hall, 2007;Welford et al, 2010).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach has been extensively applied to upper crustal problems; however, applications to the lower crust and upper mantle have been limited (e.g., Brandmayr et al 2011;Welford and Hall 2007;Welford et al 2010). Refined mesh design and sensible regularization procedures permit reasonable resolution of the Moho surface, whilst Figure 1 Tectonic map of the Tibetan Plateau (Yin and Harrison 2000).…”
Section: Structural Modeling From Seismological Tomography and Gravitmentioning
confidence: 99%
“…Refined mesh design and sensible regularization procedures permit reasonable resolution of the Moho surface, whilst Figure 1 Tectonic map of the Tibetan Plateau (Yin and Harrison 2000). Arrows denote the deformation rate from GPS measurements (Gan et al 2007 allowing variations within the crust and mantle to be modeled as part of the same procedure (Welford and Hall 2007;Welford et al 2010). The full 3D nature of this approach, along with the requirement of a large number of cells in the vertical direction, means that this method is more computationally demanding compared to other methods.…”
Section: Structural Modeling From Seismological Tomography and Gravitmentioning
confidence: 99%